The stress response of human proximal tubule cells to cadmium involves up-regulation of haemoxygenase 1 and metallothionein but not cytochrome P450 enzymes. (13th May 2016) - Boonprasert, Kanyarat; Satarug, Soisungwan; Morais, Christudas; Gobe, Glenda C.; Johnson, David W.; Na-Bangchang, Kesara; Vesey, David A.
Highlights: Cytochrome P450 (CYP P450) enzymes 2B6, 4A11, 4F2, 2E1 and 3A4 are expressed by the human kidney cortex. Primary culture of human proximal tubule cells (PTC) express CYP P450 enzymes 2E1, 3A4 and 4F2. Exposure of PTC to cadmium induces expression of the stress proteins metallothionein (MT) and haemoxygenase 1 (HO-1) but not CYP P450 enzymes. Abstract: Enzymes of the cytochrome P450 (CYP) super-family are implicated in cadmium (Cd) −induced nephrotoxicity, however, direct evidence is lacking. This study investigated the endogenous expression of various CYP proteins together with the stress-response proteins, heme oxygenase-1 (HO-1) and metallothionein (MT) in human kidney sections and in cadmium-exposed primary cultures of human proximal tubular epithelial cells (PTC). By immunohistochemistry, the CYP members 2B6, 4A11 and 4F2 were prominently expressed in the cortical proximal tubular cells and to a lesser extent in distal tubular cells. Low levels of CYPs 2E1 and 3A4 were also detected. In PTC, in the absence of Cd, CYP2E1, CYP3A4, CYP4F2 and MT were expressed, but HO-1, CYP2B6 and CYP4A11 were not detected. A range of cadmium concentrations (0–100 μM) were utilized to induce stress conditions. MT protein was further induced by as little as 0.5 μM cadmium, reaching a 6-fold induction at 20 μM, whereas for HO-1, a 5 μM cadmium concentration was required for initial induction and at 20 μM cadmium reached a 15-fold induction. The expression of CYP2E1, CYP3A4, and CYP4F2 were not altered by any cadmium concentrations tested at 48 h. Cadmium caused a reduction in cell viability at concentrations above 10 μM. In conclusion although cultured PTC, do express CYP proteins, (CYP2E1, CYP3A4, and CYP4F2), Cd-induced cell stress as indicted by induction of HO-1 and MT does not alter expression of these CYP proteins at 48 h.